Microlevel Analysis of Climate Change Adaptation and its Determinants: The Case of Smallholder Farmers in the Kembata Tembaro Zone, Southern Ethiopia - Getachew Tadesse; Mulugeta Lemenih; Teshale Woldeamanuel; Menfese Tadesse (Advances in Meteorology)
The high vulnerability of regions that predominantly rely on rain-fed agriculture to climate change and variability underscores the importance of understanding adaptation responses as a foundation for designing targeted interventions. This study investigates microlevel climate change adaptation strategies and factors determining such choices of smallholder farmers in the Kembata Tembaro Zone, southern Ethiopia. It employed a convergent parallel mixed-method research design, incorporating quantitative data collected through household surveys of 364 randomly selected smallholder farmers across diverse agro-ecological zones. This was complemented by qualitative data obtained through interviews and focus group discussions (FGDs). A multinomial logit (MNL) regression model was used to analyze the determinants of the farmers’ adaptation decisions. Nearly all respondents perceived an increase in temperature, consistent with observed trends. However, the farmers’ perception of declining rainfall corresponded only with trends during the short rainfall season (Belg). Farmers in lowland areas demonstrated greater experience with adaptation strategies and are more resilient than those in midland and highland regions. On average, 88.2% of the farmers reported implementing adaptation measures, such as adjusting planting dates, crop diversification, soil and water conservation, adopting improved livestock breeds, engagement in off-farm activities, and agroforestry practice. The regression analysis identified several significant factors influencing adaptation decisions, including age, education level, farm size, farm income, access to credit, participation in climate change training, availability of climate information, market access, and agro-ecological context. This study offers unique, context-specific insights through inter-agroecological comparisons of smallholder farmers’ adaptation choices, highlighting the complex interplay between socioeconomic and environmental variables in determining adaptation to climate change. The findings can inform policymakers when designing development policies tailored to specific local contexts.